Exploring the changing of name as a socio-cultural adaptation strategy of the Javanese Diaspora in Sabah Borneo—Malaysia - Widodo, Sahid Teguh; Suyatno, Suyatno; Mohamad, Bahtiar; Ismail, Shafinar (Frontiers in Sociology, 2025)
This research explores the evolution of personal names within the Diaspora Jawa Sabah (DJS) community, focusing on how historical events, social changes, and cultural practices have influenced DJS names, particularly after Sabah joined Malaysia in 1963. Using content analysis and in-depth interviews, the study investigates the migration history and cultural factors shaping the linguistic aspects of DJS names in Sabah. The findings reveal four key points: (1) the distinct migration histories of Javanese people to Sabah compared to the Malaysian Peninsula, (2) the impact of historical, social, and cultural phenomena on DJS names before and after 1963, (3) the transformation of DJS names into modern Malay Islamic names reflecting personal aspirations, and (4) the collective cultural and ideological shifts within the DJS community. This research contributes to the understanding of personal names as a reflection of cultural identity, illustrating the dynamic relationship between linguistic forms and broader social, historical, and cultural contexts. The study enhances the theoretical and practical knowledge of naming practices as indicators of societal changes within the DJS community.